Attempt to compromise: The Live Experience of Kermanian Fathers who have a Child, - Sheikhpourkhani, Maryam; Abbaszadeh, Abbas (Advances in Nursing & Midwifery, 2012)
Abstract Background and Aim: There is a very limited research about unique experience of fathers, who have a child, suffering from cancer at the diagnostic stage. So we seldom know anything about this experience. This study aimed to discover, live experience of kermanian fathers who have a child, suffering from cancer, at diagnostic stage. Method: This is a qualitative and phenomenology study, using purposive sampling, Data were collected via observation and semi-structured depth interview, with 7 fathers having children under 15 years old. The children were suffering from cancer and they were in ward of infant oncology department in Afzalipour hospital. Scale for samples sufficiency was saturation of data. After, recording interviews, data were coded in three stages and were contemporaneously analyzed with Colaizzi phenomenological method. Results: -Sustaining injuries with cancer diagnosis are as following: shock, denying, feeling of pain (sadness & feeling of guilt), anxiety (uncertainty). -Confrontation with cancer diagnosis includes two groups of mechanism as: optimistic mechanisms like relationship with God, cognitive redefinition) & escape mechanisms like (use of opium, increase of job commitments as multi jobs & multi shifts) -Discovery of support sources as: Rooty family and spouse Conclusion: Findings of this study, show clear picture of fathers experience in diagnostic stage of their children cancer. In addition, provide oncology nurses, with new insight and knowledge about holistic and unique cares. Limitations of the study and recommendations for further research and nursing practice improvement, has been presented. Key word: live experience, Diagnostic Stage, Childhood Cancer